Marketing Strategies in the intermediate channel and positioning for the sector of GPS marketing companies in Perú period 2018 - 2020 - León Ratto, Augusto Gerardo (2021)
The intermediate channel represents a high level of profitability for GPS marketing companies, due to their strategic alliances with insurers to obtain the database of customers who require the installation of GPS on a mandatory basis before receiving their new cars and that they will be automatically referred to your companies. Therefore, the present research aims to verify the relationship that exists between the marketing strategies of the intermediate channel and the positioning of the companies that provide GPS services throughout Peru for the period 2018 - 2020. The approach has been quantitative; non-experimental, descriptive, correlational and longitudinal design, the questionnaire being the data collection instrument that was applied in a sample of 168 clients with GPS service. Demonstrating with the results obtained, the existence of a relationship of marketing strategies oriented to the intermediate channel and the positioning of the companies that market GPS in Peru, with a Chi square value of 334.868 and a significance level of 0.001, this being very high. Therefore, the creation of strategic alliances is a necessity to obtain greater profitability in vehicle insurers and the better positioning of GPS companies.